Technology transfer, climate change mitigation, and environmental patent impact on sustainability and economic growth: A comparison of European countries - Ferreira, J.; Fernandes, C.; Ferreira, F. (Proceedings of the 10th Innovation, Entrepreneurship and Knowledge Academy, 2019)
Most of the literature on technology transfer has tended to focus on the country or regional level, neglecting to look at the continent-level flow of knowledge that is becoming more important due to regional trading blocs. This study sought to fill the gap in research on the role of technology transfer on the European continent (i.e., countries inside and outside the Eurozone) by focusing on environment-related patents. The research also included examining the effects of environmental water-related adaptation technology and climate change mitigation patents on real gross domestic product. The results contribute to the literature on technology transfer policies by highlighting how environmental patents influence Europe’s economic growth rate and whether countries’ geographical location can affect their level of entrepreneurship and innovation. The technology-organization-environment and sustainability perspectives were used as a theoretical framework for understanding how geographical contexts influence technology transfer in terms of environment-related patents. Implications for management, theory, and policy are discussed together with the study’s limitations and suggestions for future research.